PENGARUH SEARCH ENGINE OPTIMIZATION (SEO), SOCIAL MEDIA MARKETING (SMM) DAN ADVERTISING CREATIVITY TERHADAP PURCHASE INTEREST MENURUT PERSPEKTIF BISNIS ISLAM (Studi Pada Gen Z Pengguna Samsung Di Bandar Lampung) - Evita Sari; Erike Anggraeni; Is Susanto (Universitas Sarjanawiyata Tamansiswa, 2026)
This research was conducted to analyze the influence of search engine optimization, social media marketing, and advertising creativity on purchase interest conducted among Generation Z in Bandar Lampung from an Islamic business perspective. The research applied a quantitative approach to 100 respondents through purposive sampling techniques. The data analysis used was SEM-PLS to examine the influence among variables. The research findings proved that search engine optimization did not have a significant influence on purchase interest. Social media marketing had a significant influence on purchase interest. Advertising creativity did not have a significant influence on purchase interest. Indicating that Generation Z is more responsive to social media marketing compared to search engine optimization and advertising creativity. From the Islamic business perspective, all three are required to uphold the values of transparency, honesty, and responsibility to build rational consumer purchase interest in accordance with Islamic business principles.